2009
DOI: 10.1097/ede.0b013e31819463bd
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Road Traffic Noise and Myocardial Infarction

Abstract: The results lend some support to the hypothesis that long-term exposure to road traffic noise increases the risk for MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
182
6
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(206 citation statements)
references
References 28 publications
13
182
6
5
Order By: Relevance
“…The final exposure estimate combined the levels from distant and nearby roads. The noise assessment is described in detail elsewhere (41). In our analyses, the variable was dichotomized at the 75 th percentile (51.8 dBA).…”
Section: Noise and Air Pollution Exposure Assessmentmentioning
confidence: 99%
“…The final exposure estimate combined the levels from distant and nearby roads. The noise assessment is described in detail elsewhere (41). In our analyses, the variable was dichotomized at the 75 th percentile (51.8 dBA).…”
Section: Noise and Air Pollution Exposure Assessmentmentioning
confidence: 99%
“…Certain environmental factors in urban settings, such as air pollution, noise and extreme high temperatures have been associated with increased mortality (Selander et al 2009;Basagaña et al 2011;Hoek et al 2013). Some studies have suggested that natural outdoor environments might help reducing the levels of air pollution and noise, as well as extreme temperatures in cities, and therefore reduce the impact of these environmental factors on our health and life-expectancy (Shanahan et al 2015;Wolf and Robbins 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many authorities around the world tend to underestimate the harmful effects of noise pollution compared to other types of pollution such as water, land, or air pollution. Nevertheless, recent research shows that noise pollution can pose serious risks to health such as hypertension [1][2][3], annoyance [4], sleep disturbance [5], and myocardial infarction [6,7].…”
Section: Introductionmentioning
confidence: 99%